An efficient tandem approach for the synthesis of functionalized 2-pyridone-3-carboxylic acids using three-component reaction in aqueous media - Mehrparvar, Saber; Rominger, Frank (Molecular diversity, 2014)
Novel analogs of 2-pyridone-3-carboxylic acids 4a-l have been prepared by the three-component reaction of 3-formyl chromone, Meldrum’s acid, and primary amines in the presence of a catalytic amount of diammonium hydrogen phosphate in water. Good-to-high yields, easy work-up, and an environmentally friendly profile are the advantages of this method for the synthesis of 2-pyridone-3-carboxylic acid derivatives.
Gesehen am 24.07.2020